2011
DOI: 10.3109/00365521.2011.565069
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct types of cancer of different origin may be mixed in gastroesophageal junction adenocarcinomas in Japan: Evidence from direct evaluation of gastric acid secretion

Abstract: Two distinct types of cancer of different origin may be mixed in GE junction adenocarcinomas. One is Barrett's esophageal cancer associated with high gastric acid secretion and reflux of gastric acid into the esophagus, the other is cancer resembling distal gastric cancer associated with gastric atrophy and low gastric acid secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
2
29
0
1
Order By: Relevance
“…In our study, the rate of H. pylori infection was significantly lower in patients with cardiac cancer than in patients with distal gastric cancer. Previous reports [24,45] support our results. Our study also revealed that the prevalence and degree of corporal gastritis were significantly lower in patients with GEJA than in patients with distal gastric cancer.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, the rate of H. pylori infection was significantly lower in patients with cardiac cancer than in patients with distal gastric cancer. Previous reports [24,45] support our results. Our study also revealed that the prevalence and degree of corporal gastritis were significantly lower in patients with GEJA than in patients with distal gastric cancer.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, Horii et al [24] investigated the relationship between GEJA and gastric acid secretion using the endoscopic gastrin test. They demonstrated that 2 distinct types of cancer of different origin may be mixed in GEJA, including Barrett’s esophageal cancer, which is associated with high gastric acid secretion and reflux of gastric acid into the esophagus, and a cancer resembling distal gastric cancer associated with gastric atrophy and low gastric acid secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intubation tests with direct measurement of acid secretion in patients with gastric cancer have only exceptionally been performed and a varying degree of impaired acid secretion has been reported in early gastric cancer [38]. However, atrophic gastritis is the most frequent precursor of gastric cancer and there is substantial indirect evidence of acid hyposecretion in intestinal-type gastric cancer by the determination of serum biomarkers [39,40,41,42].…”
Section: Acid Secretion and Gastric Cancermentioning
confidence: 99%
“…The same group proposed that the preservation of gastric acid secretion might be important for the development of adenocarcinoma at the EGJ (including EAC) in Japanese people, irrespective of the H. pylori infection status [91]. Namely, there may be two distinct types of cancer at the EGJ-EAC (BE cancer) associated with high gastric acid secretion and reflux of gastric acid into the esophagus and EGJ adenocarcinoma (non-BE cancer) resembling distal gastric cancer associated with gastric atrophy and low gastric acid secretion [92,93].…”
Section: H Pylori Infection and Carcinogenesismentioning
confidence: 99%